2023
DOI: 10.3390/su15118475
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emissions in Transportation: A Synthesis Framework

Abstract: With the growing concern worldwide regarding greenhouse gas (GHG) emissions and their impacts on human health and the environment, transportation has become a central theme in their mitigation, responsible for 15% of anthropogenic GHG, 23% of global energy-related, and 8.7 Gt CO2-eq emissions. This study’s objective was to comprehensively review the current state of carbon mitigation in the transportation sector. This was conducted through a systematic literature review based on the multi-level perspective of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Zhu et al (2012) provided an early foray into the effectiveness of road dust emission control measures [22]. Studies have paved the way for more comprehensive reviews, such as those conducted by Ferrer and Thomé (2023), which underscores the need for transportation services to adapt to climate change imperatives [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhu et al (2012) provided an early foray into the effectiveness of road dust emission control measures [22]. Studies have paved the way for more comprehensive reviews, such as those conducted by Ferrer and Thomé (2023), which underscores the need for transportation services to adapt to climate change imperatives [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is documented evidence about enablers and barriers of reducing carbon emissions in transportation, with the main categories being technological innovations (e.g., electrification and alternative fuels), operational measures (e.g., vehicle routing and intermodal transportation), regulatory and economic measures (e.g., urban governance), urban form and human behavior (e.g., modal shift and shared mobility), and strategy and stakeholder pressure (e.g., business strategies and carbon polices) [3]. Regarding human behavior, the preferences for the use of individual cars prevail over shared mobility, public transportation, and less-polluting transport modes such electric bikes [3]. Regarding the university context, previous studies indicated that the car was the main means of transport to university in Spain [4], and that most students were passive commuters [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Given the aforementioned health and environmental benefits associated with AC, initiatives and policies that encourage PA and reduce greenhouse gas emission are required for the university population. For this purpose, understanding the influences on this behavior is essential to designing effective measures since each urban area is particular in many ways (e.g., geography, infrastructure, and socioeconomic characteristics), and, as a result, has specific transportation challenges [3]. The choice of the mode of transportation depends on multifactorial variables.…”
Section: Introductionmentioning
confidence: 99%